Working with English grammar : an introduction - Cummings, Louise (Cambridge University Press, 2018)
"This clear and concise introduction offers students of linguistics and English language a comprehensive overview of English grammar, including word structure, major and minor word classes, phrases, clauses, and sentences. Based on twenty years' teaching practice, Louise Cummings adopts a unique approach of using three real-world contexts - first language acquisition, language disorders, and non-standard dialects - as a pedagogical tool to make grammatical concepts meaningful to students and to improve engagement and understanding. In seven accessible chapters, students are encouraged to develop the analytical skills they require to give a comprehensive description of the grammar of the English language"-- Provided by publisher.